THE FAMILY AS THE CRADLE OF UPBRINGING (Web of Teachers: Inderscience Research, 2025)
In the article, the author showed that the place of the family in society is multifaceted, but at present the most important task of the family is to educate, for society, a person ready for public life, having his own opinion and worldview. The author showed that the right atmosphere in the family will be a guide for the child's future life, otherwise the behavior of a child who grew up in the wrong environment cannot be corrected by any social institutions. It is in the family that the personality of a child grows up, self-confident, able to correctly interpret universal human relations in society and give others the love and care that existed in the family. On the contrary, crime, delinquency, neglect of education among modern youth is revealed by the author as a consequence of increasing family disunity, depriving children of parental or maternal love. The presentation of comparative examples shows the scientific and practical significance of the article.